Changes in cosmic radiation doses of aircraft crew over the COVID-19 pandemic (2019–2022) - Yasuda, Hiroshi; Yajima, Kazuaki (Frontiers in Public Health, 2025)
The in-flight cosmic radiation exposure of crew members in commercial jet aircraft is considered occupational exposure. In Japan, a guideline for the management of in-flight exposure of aircraft crews was established in 2006 by the radiation council. Accordingly, in-flight doses of aircraft crews have been calculated, and their annual in-flight doses have been recorded for the last 18 years, for which the authors have cooperated with airlines to calculate aviation route doses on a monthly basis. In this brief report, we present the trend of annual dose distributions of cabin attendants (CAs) and pilots (PLs) working in one of the Japanese airlines over the period of the COVID-19 pandemic from fiscal year 2019 to 2022. The cosmic radiation exposure of the CAs was significantly affected by the pandemic. The percentage of the CAs who annually received >1 mSv sharply decreased from 65% in the pre-pandemic year (2019) to 4.6% in the first year of the pandemic (2020), and their collective doses notably decreased in 2020 to 30% of the pre-pandemic level, followed by gradual recovery in subsequent two years. In contrast, the annual dose distribution of the PLs did not show a notable change, which is attributable to the increase in cargo flights and the introduction of small aircrafts during the pandemic.